O garantismo penal de ferrajoli e suas consequências para os índices delitivos do estado brasileiro - Gomes, Antônio Igor Félix (Universidade Federal Rural do Semi-Árido, 2019)
Given the current epidemic violence in Brazilian society, this article aims to point out evidence that Luigi Ferrajoli's Criminal Guarantee has contributed negatively to the increase in the country's violent rates, according to facts that point to adverse conditions, the state jus puniendi, so that it would be possible to ascertain whether its restriction on the homeland criminalist culture would have the potential to have positive consequences on such indices. For this, we used the method of exploratory investigations through bibliographical research of literary works focused on philosophy, history, political science, as well as legal sciences that deal directly with the subjects covered in this work. Articles and scientific studies on the issue, published in periodical magazines or in media outlets, and finally, official indexes on the history of violence in Brazil were used for contextualization and correlation. As a result, it was found that the strong evolution of violent crime rates in Brazil begins from the advent of CF / 1988, remaining sustainably high until today and during this period, the culture of guarantee in the Brazilian criminal milieu spread. Suggesting concause relationship. Evidence has been found that, in the meantime, new developments and peaks in the history of such indices are always observable in the years immediately following each time the legal institutes approached here, of strong national repercussion and overly guaranteeing in nature, were applied in the penal order. By examining the thought and ideology that shapes Luigi Ferrajoli's worldview, as well as his proposed Minimum Criminal Law, some of his, radical short-, medium- and long-term programmatic objectives and revolutionary aims towards construction are verified of an ―evolved society‖, having in Minimum Criminal Law a tool for this, suggesting the potential to bring unpredictable and harmful consequences to the security of society, undermining its effectiveness as a right of the population and duty of the state. Moreover, according to indications shown, it is pointed out that Criminal Guarantee is undermining the public security of the country from the moment that makes the Brazilian criminal justice condescending and lenient with crime. Conclusively, this study, with the strong indications brought, contributes to the prelude to a growing discussion and strong reflection on the need to rethink and urgently limit the predominance of the ideological culture of Criminal Guarantee, as proposed by Luigi Ferrajoli in the legal activities of the operators of the Brazilian repressive system as a first act to enable conditions that allow the rates of national public violence to regress to the least reasonable levels.
Monografia
Keywords: Evidências; Garantismo Penal; Ferrajoli; Índices de Criminalidade; Evidence; Criminal Guarantee; Ferrajoli; Crime Indexes; CIENCIAS SOCIAIS APLICADAS::DIREITO